Partial Fibular Head Osteotomy is an Alternative Option in Treatment of Posterolateral Tibial Plateau Fractures: A Retrospective Analysis - Lu, Yao; Wang, Gen; Ren, Cheng; Xu, Yibo; Huang, Qiang; Fan, Shan; Li, Ming; Zhang, Kun; Li, Zhong; Wang, Qian; Ma, Teng (Frontiers in Surgery, 2022)
Objective: This study aimed to evaluate the short-term effects of partial fibular head osteotomy for treating posterolateral tibial plateau fractures. Methods: A retrospective analysis was performed on 25 patients with posterolateral tibial plateau fractures who were treated using a partial fibular head osteotomy approach. Computed tomography was performed for fracture typing and evaluation. The mode of injury, time from injury to surgery, time for fracture union, range of motion of the knee, and complications were recorded. Knee joint function was evaluated using the Hospital for Special Surgery Mayo Score (HSS). Results: The mean follow-up period was 21.5 (range, 12–36) months. Fracture united in all patients and the average clinical healing time for fractures was 11.2 ± 1.9 (range, 8–16) weeks. The mean time from injury to surgery was 3.1 ± 1.8 (range, 1–10) days. The mean range of flexion was 131.6° ± 12.5° (range, 110°–145°). The mean range of extension was 1.4°–4.2° (range, -5°–10°). The mean HSS at the final follow-up was 93.5 ± 5.4 (range, 79–100). None of the patients exhibited symptoms of common peroneal nerve injury, knee instability, or upper tibiofibular joint injury. One patient had a superficial infection and was treated with surgical dressing. Conclusion: The partial fibular head osteotomy approach is a feasible alternative for treating posterolateral tibial plateau fractures.